Indirect gas fired forced convection air heaters with rated heat inputs up to 2 MW for industrial and commercial space heating : safety and performance requirements (exeluding electrical requirements) (2nd family gases) - 8096 British Standards Institution (London : BSI, 1989)
PSZJBL